CHINESE MOBILE PAYMENT LANDSCAPE: A STIMULUS ORGANISM RESPONSE MODEL EXAMINING PERCEIVED VALUE, SATISFACTION, AND INFLUENCES ON CUSTOMERS’ WILLINGNESS ON THIS TECHNOLOGY - Chen, Shulan; Chaveesuk, Singha; Chaiyasoonthorn, Wornchanok (My University, 2024)
This study aims to identify factors influencing individuals’ willingness to use mobile payment applications in China. Stimulus–organism–response (SOR) theory served as the foundational framework. Quantitative data were collected from 462 valid questionnaire addressing people’s use of mobile payment platforms in various regions of China. Structural Equation Modeling (SEM) results that perceived usefulness and ease of use significantly increase user satisfaction and perceived value. In the same vein, service quality and social influence also positively and significantly influence to satisfaction. In other words, cost has negative and significant impact on perceived value. Perceived value has positive and significant impact on satisfaction. Perceived value and satisfaction have positive and significant impact on willingness to use. The current study with significant findings contributed to fill the gap in the context of China region because only a few studies leveraged the SOR theory to explore mobile payment. The findings also contributed to enrich knowledge of mobile payment applications and provide actionable guidance to help mobile payment operators make strategic decisions. These results could also increase the understanding of mobile payment which paint a more vivid picture of this phenomenon and can enable mobile payment operators to make better strategic choices.
Keywords: China; Investigation; Mobile Payment; SOR Theory; Willingness to use